PORTFOLIO METHOD OF SCIENTIFIC ACTIVITY MANAGEMENT OF HIGHER EDUCATION INSTITUTIONS - Varvara Piterska; Oleh Lohinov; Liliia Lohinova (Сучасний стан наукових досліджень та технологій в промисловості)
The subject matter of the article is models and methods of portfolio management of research projects of higher education institutions. The goal of the work is to create methods of portfolio management of scientific activities of institutions of higher education on the example of the Odessa National Maritime University. The following tasks were solved in the article: analysis of the innovation model of state development, the formation of a model for managing the scientific activities of higher education institutions, the development of a method for forming a portfolio of research projects of a higher education institution using the example of Odessa National Maritime University. The following methods used are – project and program management methods, systems theory and systems analysis, mathematical modeling methods. The following results were obtained – developed mechanisms for scientific projects management of higher educational institutions, developed a method for forming a portfolio of scientific projects of a higher education institution that takes into account the strategic goals of the university and available resources. Conclusions: using the portfolio management method of research projects of a higher education institution allowed the university to increase the effectiveness of scientific activities, form an effective portfolio of research projects, based on determining the organization’s planned trajectory length when implementing strategic research goals, allowed the university to achieve its strategic goal as part of an innovative program mission. Based on the proposals received for each research project, the specific length of the trajectory was determined as the ratio of the length of the trajectory to be held by the institution of higher education (Odessa National Maritime University) in case of successful implementation of a certain scientific project to the planned trajectory length. On the basis of the proposed system of management of scientific activities of higher education institutions, which has a four-level structure, temporary standards for the implementation of research projects in the portfolio of higher education institutions are distributed. Comparative assessments of research projects of Odessa National Maritime University have been obtained, allowing to include in the portfolio scientific projects "SP3", "SP2", "SP1", which contribute to the achievement of the strategic goal of the university as part of the mission of the innovation program.